Taming Polysulfides in an Li–S Battery With Low-Temperature One-step Chemical Synthesis of Titanium Carbide Nanoparticles From Waste PTFE - Liu, Suyao; Luo, Jun; Xiong, Yuting; Chen, Zhe; Zhang, Kailong; Rui, Guofeng; Wang, Liangbiao; Hu, Guang; Jiang, Jinlong; Mei, Tao (Frontiers in Chemistry, 2021)
In this work, titanium carbide (TiC) nanoparticles have been successfully synthesized at much lower temperatures of 500°C using cheaper starting materials, such as waste polytetrafluoroethylene (PTFE) (carbon source) and titanium and metallic sodium, than the traditional carbothermal reduction of TiO2 at 1,800°C. An XRD pattern proved the formation of face-centered cubic TiC, and TEM images showed the obtained TiC nanoparticles with an average size of approximately 50 nm. In addition, the separator coated with TiC nanoparticles as an active material of interlayer effectively mitigates the shuttling problem by taming the polysulfides in Li–S batteries compared with a traditional celgard separator. The assembled cell realizes good cycling stability with 501 mAh g−1 and a low capacity fading of 0.1% per cycle after 300 cycles at 1 C due to high utilization of the sulfur-based active species.